2017
DOI: 10.1021/acs.joc.7b01837
|View full text |Cite
|
Sign up to set email alerts
|

Constitutional Isomers of Pentahydroxy-Functionalized Pillar[5]arenes: Synthesis, Characterization, and Crystal Structures

Abstract: We herein report the preparation of constitutional isomers of pentahydroxy-functionalized pillar[5]arenes via the deprotection of their benzylated derivatives by catalytic hydrogenation. The structures of the obtained isomers were then established using single crystal X-ray diffraction. We also found that the yield distribution of the different constitutional isomers was dependent on the nature of the substitution, as revealed by HPLC analysis of the crude mixture. Finally, further characterization of the sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…52 Initially, allyloxy-functionalized rim-differentiated P [5] was synthesized 51 for subsequent selective removal of allylic groups; however, C 5 -symmetric pentahydroxy P [5] was first successfully produced by hydrogenolysis of the corresponding pentabenzyloxy derivative by Al-Azemi and coworkers. 50 Their reported 1% yield, owing to statistical cyclization and nontrivial isolation, prevented potential development of this compound. This is where our preoriented synthetic protocol came to the rescue.…”
Section: Functionalizing C 5 -Symmetric Pillar[5]arenes At Willmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Initially, allyloxy-functionalized rim-differentiated P [5] was synthesized 51 for subsequent selective removal of allylic groups; however, C 5 -symmetric pentahydroxy P [5] was first successfully produced by hydrogenolysis of the corresponding pentabenzyloxy derivative by Al-Azemi and coworkers. 50 Their reported 1% yield, owing to statistical cyclization and nontrivial isolation, prevented potential development of this compound. This is where our preoriented synthetic protocol came to the rescue.…”
Section: Functionalizing C 5 -Symmetric Pillar[5]arenes At Willmentioning
confidence: 99%
“…Cao and Meier demonstrated that the four constitutional isomers were obtained in amounts that were close to the statistical 5:5:5:1 ratio, in which the rim-differentiated P [5] is the least abundant product, accounting only for one-sixteenth of all P [5] isomers. 39a Even though the work of Huang 39b and Al-Azemi 50 showed that the probability of obtaining these isomers can deviate from the idealized binomial distribution, the relatively low concentration of rim-differentiated P [5]s in the crude product still led to nontrivial purification processes, which often involved preparative high-performance liquid chromatography.…”
Section: Synpacts Syn Lettmentioning
confidence: 99%
“…Chemical modification of the pillararene system could be achieved in two ways, namely cyclization of appropriately functionalized monomers or functionalization of preformed pillararenes (Al-Azemi et al, 2017). In the former, co-cyclization of pre-functionalized monomers in an appropriate feed ratio could be employed to generate pillararenes having the desired functionalities in terms of numbers and positions.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Supramolecular polymers constructed by reversible noncovalent interactions such as hydrogen bonds, metal-ligand interactions, host-guest interactions,interactions and van der Waals forces have gained considerable interest for their intriguing properties of recycling and responsiveness to external stimuli (Raghupathi et al, 2014;Takashima et al, 2017). Pillararenes are unique three-dimensional macrocyclic compounds which possess symmetric rigid structures and are easy to functionalize with various substituents (Ogoshi et al, 2008;Al-Azemi et al, 2017). They exhibit outstanding abilities to selectively bind different kinds of guest molecules and thus are excellent host molecules for guest encapsulation and molecular recognition.…”
Section: Chemical Contextmentioning
confidence: 99%